2005
DOI: 10.1021/jf0490145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extrusion, Boiling, Autoclaving, and Microwave Heating on Lupine Allergenicity

Abstract: Lupine flour has been reported as a causative agent of allergic reactions. However, the allergenicity of lupine after thermal processing is not well-known. For this purpose, the allergenic characteristics of lupine seeds after boiling (up to 60 min), autoclaving (121 degrees C, 1.18 atm, up to 20 min and 138 degrees C, 2.56 atm, up to 30 min), microwave heating (30 min), and extrusion cooking were studied. The IgE-binding capacity was analyzed by IgE-immunoblotting and CAP inhibition using a serum pool from 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
72
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 28 publications
13
72
3
Order By: Relevance
“…During digestion peptide bonds are cleavaged, which results in protein structure changes. Such changes may cause the formation of new epitopes or uncovering antigenic determinants, initially hidden inside protein structures [11]. The trypsin activity resulted in complete loss of immunoreactivity of lupin seed proteins (Fig.…”
Section: Antigenic Properties Of Lupin Seed Proteins and Their Hydrolmentioning
confidence: 99%
See 2 more Smart Citations
“…During digestion peptide bonds are cleavaged, which results in protein structure changes. Such changes may cause the formation of new epitopes or uncovering antigenic determinants, initially hidden inside protein structures [11]. The trypsin activity resulted in complete loss of immunoreactivity of lupin seed proteins (Fig.…”
Section: Antigenic Properties Of Lupin Seed Proteins and Their Hydrolmentioning
confidence: 99%
“…There is limited information describing change of antigenicity of lupin proteins during technological processing. The available data provide insight into immunoreactivity changes during heat treatment of lupin seed proteins [11]. Álvarez-Álvarez et al [11] analysed the effect of extrusion cooking, boiling, autoclaving, and microwave heating on the lupin seed proteins stability.…”
Section: Antigenic Properties Of Lupin Seed Proteins and Their Hydrolmentioning
confidence: 99%
See 1 more Smart Citation
“…The main protein binding IgE of allergic characterised by molecular weights in the range of: 45-42 kDa [10,13,14]. Other potential allergens may be a protein with the molecular weight of 13 kDa [10], 29 kDa [15], 34 kDa [16], 38 kDa [12] and 66 kDa [17].…”
Section: Introductionmentioning
confidence: 99%
“…Álvarez-Álvarez et al [15] analysed the influence of extrusion cooking, autoclaving and microwave heating on the stability of lupin seed proteins. On the basis of the immunoblotting analysis, they found that only the autoclaving process causes a significant change in the amount of proteins that interact with the antibodies of people who were allergic to lupin.…”
Section: Introductionmentioning
confidence: 99%